Application of Problem Based Learning Model in Improving the Learning Outcomes of Islamic Religious Education on the Theme of the Content of the Qur'an Surah Al-Maun - Mutmainah (Research Journal on Teacher Professional Development, 2025)
This study aims to analyze the effectiveness of the application of the Problem Based Learning (PBL) learning model in improving the learning outcomes of grade 5 students in the material Understanding the Basic Message of Q.S. Al-Ma'un at SDN Geneng 1. The background of this research is the low learning outcomes caused by the lack of innovative learning methods and the lack of active student involvement. The research was carried out through a qualitative approach with a Class Action Research (PTK) design consisting of three cycles, including the planning, implementation, observation, and reflection stages. The research subjects are grade 5 students, with a focus on improving learning outcomes and learning activities during the learning process. The results showed a significant increase in the average score from the initial condition (51.4) to 64.3 (cycle I), 71.4 (cycle II), and 85.71 (cycle III). Learning completeness also increased from 28.5% to 57.14%, 71.42%, to 85.71%. Student learning activities increased from 70.59% (cycle I) to 85.71% (cycle III), showing that PBL has succeeded in increasing students' engagement, motivation, and critical thinking skills. Thus, the application of the PBL model has proven to be effective in improving the understanding of the material as well as students' attitudes and learning motivation in the subjects of Islamic Religious Education and Ethics